The effect of an educational video on long-acting reversible contraception (LARC) utilization at 6–8 weeks postpartum period: a randomized controlled trial - Chada Burapasikarin (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. Purpose: Long-acting reversible contraception is highly effective in preventing unintended pregnancy and unsafe abortion. An educational video administered during early postpartum period might be an effective tool to improve postpartum LARC use. The objectives were to evaluate whether a postpartum educational video about LARC could increase postpartum LARC utilization at 6–8 weeks postpartum and to assess why postpartum women did not receive LARC. Methods: This randomized-controlled trial was conducted at the postpartum unit of a university Hospital between August 2016 and February 2017. Postpartum women who were aged > 20 years and willing to participate were recruited. Participants allocated to the study group watched the 7-min educational video on LARC methods while the control group did not. To assess LARC utilization, data were collected at 6–8 weeks postpartum using telephone calls and/or medical record review to determine postpartum contraception use and reasons for not using LARC. Results: Two-hundred and seventy participants were enrolled, and the video (135) and non-video (135) groups had similar baseline characteristics. In the video group, 57.8% (95% CI 49.0–66.2) reported using a LARC method, compared to 25.9% (95% CI 18.8–34.2) in the non-video group (p < 0.05). The reasons for not using LARC in both groups were inconvenience of access (42.0–43.8%) and uncertainty about methods (17.0–24.6%). Conclusion: The educational video introduced at immediate postpartum period was efficacious in increasing the utilization of LARC at 6–8 weeks postpartum. Inconvenience of access was the most common reason cited for not using LARC. Clinical trial registration number: Clinicaltrials.in.th TCTR20171225001 “retrospectively registered”.